Implementation of Controlled Robot for Fire Detection and Extinguish to Closed Areas Based on Arduino - Ihsan A. Taha; Hamzah M. Marhoon (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The wireless control systems are taking a special importance in the recent years, where the wireless control system provide several advantages; including the disposal of the using wire and periodic maintenance of data transmission wires, in the science of robot wireless control unit is the main part of the fire treatment and extinguish robot system. The lives of firefighters exposed to the risk of death and Rima, therefore the use of remote control systems more secure is necessary. In this, paper a fire-extinguish robot used for extinguishing the fire in general and in treatment fires in the closed areas for protecting employees in the field of fire suppression from combustion, exposure or inhalation to the toxic gases. The basic idea of fire detection and treatment robot based on detect the fire by the wireless camera and flame sensor then suppression the fire by send command from mobile phone through Bluetooth connection to make water pump turn "ON", and the fire then extinguished.